2011
DOI: 10.3109/17549507.2011.595825
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based practice in speech-language pathology curricula: A scoping study

Abstract: This scoping study investigated how evidence-based practice (EBP) principles are taught in Australian speech-language pathology (SLP) teaching and learning contexts. It explored how Australian SLP university programs: (1) facilitate student learning about the principles of EBP in academic and clinical settings, and (2) self-evaluate their curricula in relation to EBP. The research involved two surveys. Survey 1 respondents were 131 academic staff, program coordinators, and on-campus and off-campus clinical edu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Students often perceive a gap between what they are learning about EBP in the classroom and its clinical application (e.g., Alverson & Greenwald, 2009). Togher et al (2011) validated this finding by reporting a disconnect between how EBP is addressed in academic courses and in clinical education. They found that whereas EBP is intentionally taught in academic courses, there is no such emphasis in clinical education.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…Students often perceive a gap between what they are learning about EBP in the classroom and its clinical application (e.g., Alverson & Greenwald, 2009). Togher et al (2011) validated this finding by reporting a disconnect between how EBP is addressed in academic courses and in clinical education. They found that whereas EBP is intentionally taught in academic courses, there is no such emphasis in clinical education.…”
mentioning
confidence: 72%
“…In a survey of Australian SLPs, Togher et al (2011) reported some encouraging trends regarding SLPs' awareness of and attitudes toward EBP. The results strongly suggested that professionals (both academic and clinical) enthusiastically embraced EBP but showed some significant shortcomings in bridging the gap between EBP knowledge and clinical application.…”
Section: Transitioning From Academic Knowledge Of Ebp To On-campus CLmentioning
confidence: 99%
“…Similar approaches have been reported in the literature such as problem-based and case-based teaching 38,39 . A review of pre-registration EBP teaching in Australia also reported the use of strategies and resources to support the application of EBP to clinical practice, with proportionally more time spent on the application of EBP knowledge than teaching EBP concepts 40 .…”
Section: __________________________________ Insert Figure II About Herementioning
confidence: 99%
“…A barrier to the implementation of these principles appears to be SLPs' awareness and ability to apply these principles to treatment (Conway & Walshe, 2015). However, Togher et al (2011) commented that awareness of evidencebased practice and positive attitudes associated with this do not necessarily result in changes to clinical practice. It is important to determine if the principles of motor learning have been similarly received by Australian SLPs.…”
Section: Introductionmentioning
confidence: 99%